1997
DOI: 10.1038/385343a0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by insulin of a unique neuronal Ca2+ pool and of neuropeptide secretion

Abstract: The insulin receptor is a tyrosine kinase receptor that is found in mammalian brain and at high concentrations in the bag cell neurons of Aplysia. We show here that insulin causes an acute rise in intracellular Ca2+ concentration ([Ca2+]i) in these neurons and triggers release of neuropeptide. The insulin-sensitive intracellular Ca2+ pool differs pharmacologically from previously described Ca2+ stores that are sensitive to inositol trisphosphate and from mitochondrial Ca2+ stores. Insulin, but not thapsigargin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 25 publications
4
67
1
2
Order By: Relevance
“…On the other hand, the relative weight of the reproductive organ to the whole body weight was unaffected by the LGC removal (Geraerts 1992). In Aplysia, the bag cells, neurosecretory cells that produce egg-laying hormone (ELH), contain insulin receptors and application of mammalian insulin to the bag cells results in a large increase in the intracellular Ca 2+ concentration and triggers the secretion of ELH (Jonas et al 1997). Considering these results, we cannot rule out a role for oIRP in the regulation of gametogenetic development.…”
Section: Stages Of Gonad Development*mentioning
confidence: 99%
“…On the other hand, the relative weight of the reproductive organ to the whole body weight was unaffected by the LGC removal (Geraerts 1992). In Aplysia, the bag cells, neurosecretory cells that produce egg-laying hormone (ELH), contain insulin receptors and application of mammalian insulin to the bag cells results in a large increase in the intracellular Ca 2+ concentration and triggers the secretion of ELH (Jonas et al 1997). Considering these results, we cannot rule out a role for oIRP in the regulation of gametogenetic development.…”
Section: Stages Of Gonad Development*mentioning
confidence: 99%
“…An example of this occurs in bag cell neurons (BCNs) of Aplysia californica, which, in response to brief stimulation, undergo long-lasting changes in excitability and secretion that alter reproductive behaviors (Conn and Kaczmarek, 1989). These changes are caused by activation of protein kinases that modulate ion currents, enlarge secretory endings and cause movement of secretory granules to sites adjacent to calcium channels, in preparation for neuropeptide release (Kaczmarek et al, 1980;Azhderian and Kaczmarek, 1990;Fisher and Kaczmarek, 1990;Wilson and Kaczmarek, 1993;Jonas et al, 1997;Wayne et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike its peripheral counterpart, insulin/insulin receptor in the brain does not appear to exert a direct effect on neuronal glucose metabolism, but most likely plays a modulatory role, via activating specific signal transduction cascades, in synaptic activities involved in memory formation. Evidence has shown that insulin/ insulin receptor is involved in regulation of neurotransmitter release (Bhattacharya and Saraswati 1991;Figlewicz and Szot 1991), receptor conductance and trafficking (Wan et al 1997;Beattie et al 2000;Lin et al 2000;Man et al 2000;Skeberdis et al 2001;Zhou et al 2001), and intracellular Ca 2+ release and neuropeptide secretion (Jonas et al 1997). As a receptor tyrosine kinase, the insulin receptor in the hippocampus was shown to respond to learning experiences by alterations in its gene expression and activation of downstream molecules such as Shc/Erk1/2 in an early stage of memory formation (Zhao et al 1999).…”
mentioning
confidence: 99%